2012
DOI: 10.2319/080911-501.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of root resorption between self-ligating and conventional preadjusted brackets using cone beam computed tomography

Abstract: Although EARR has occurred in all teeth evaluated, the bracket design (self-ligating or conventional) did not demonstrate any influence on the results observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 28 publications
(79 reference statements)
6
52
1
6
Order By: Relevance
“…The full-texts of the reserved ten studies were retrieved and assessed referring to the inclusion and exclusion criteria. Finally, seven studies [1723] fulfilled the criteria and were included in present systematic review, five of which [1721] were pooled for meta-analysis. A flow diagram of the study selection process was demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The full-texts of the reserved ten studies were retrieved and assessed referring to the inclusion and exclusion criteria. Finally, seven studies [1723] fulfilled the criteria and were included in present systematic review, five of which [1721] were pooled for meta-analysis. A flow diagram of the study selection process was demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…38 A previous investigation of OIIRR differences between two bracket systems adopted a difference of 0.4 mm as being clinically significant to calculate sample size. 42 A post-hoc power calculation after code breaking for the secondary outcome of OIIRR, using the above mentioned difference, a root mean squared error incorporating the variance of the OIIRR from the present trial and a 5% level of significance indicated that the present trial would have a power of 25-30%.…”
Section: Sample Size Calculationmentioning
confidence: 93%
“…-randomized trials have been done but there are too few 14,24,29,38 ; -samplings are low 24,29,36 ; -systematic reviews and metaanalyses only allow us to assess a few high caliber articles 16,30 . In addition, it is important to note that most of the studies were carried out with just a few bracket models even though there are many different brands: Smart Clip TM (3M Unitek, Monrovia, Calif) 4 …”
Section: Discussion On the Selected Articlesmentioning
confidence: 99%